Features of Microbial Landscape and Antimicrobial Chemotherapy in Patients with Non-Lactational Mastitis - K. V. Lipatov; E. A. Komarova; M. A. Mirskaya; V. I. Khrupkin; M. A. Kiryupina (Антибиотики и Химиотерапия, 2020)
The article analyzes the results of a microbiological examination of 336 patients with various forms of non-lactating mastitis. The causative agent was identified in 321 (95.5%) patients. Monoculture was identified in the majority of observations (84.4%), microbial associations were found in 15.6% of cases. Staphylococcus aureus had prevailed as the causative agent (69.7% of cases). Microflora composition depended on the form of the disease: S.aureus was isolated from the samples in 86.1% of cases of acute form of non-lactating mastitis, in 69.8% of cases of subacute form, and in 57.4% of patients with chronic form of non-lactating mastitis. The role of gram-negative microorganisms and microbial association is constantly evolving. The frequency of isolation of multiple antibioticresistant strains of microorganisms depended on the duration of the disease, the previous intake of antibacterial drugs and the clinical course of the disease. In acute forms of non-lactating mastitis methicillin-resistant S.aureus (MRSA) was isolated in only 2% of cases among all isolated S.aureus, while in subacute and chronic forms of the disease the frequency of MRSA isolation dramatically increased to 11.7% and 23.4% of all strains of staphylococci, respectively.Microbiological monitoring of wound fluid in the treatment of patients with non-lactating mastitis in combination with rational antibiotic therapy and adequate surgical intervention is the key to successful treatment of this category of patients.